Understanding Overuse of Computed Tomography for Minor Head Injury in the Emergency Department: A Triangulated Qualitative Study - Melnick, Edward R.; Shafer, Katherine; Rodulfo, Nayeli; Shi, Joyce; Hess, Erik P.; Wears, Robert L.; Qureshi, Rija A.; Post, Lori A.; Biros, Michelle (Academic emergency medicine, 2015)
Background Overuse of computed tomography (CT) for minor head injury continues despite developed and rigorously validated clinical decision rules like the Canadian CT Head Rule (CCHR). Adherence to this sensitive and specific rule could decrease the number of CT scans performed in minor head injury by 35%. But in practice, the CCHR has failed to reduce testing, despite its accurate performance. Objectives The objective was to identify nonclinical, human factors that promote or inhibit the appropriate use of CT in patients presenting to the emergency department (ED) with minor head injury. Methods This was a qualitative study in three phases, each with interview guides developed by a multidisciplinary team. Subjects were recruited from patients treated and released with minor head injuries and providers in an urban academic ED and a satellite community ED. Focus groups of patients (four groups, 22 subjects total) and providers (three groups, 22 subjects total) were conducted until thematic saturation was reached. The findings from the focus groups were triangulated with a cognitive task analysis, including direct observation in the ED (>150 hours), and individual semistructured interviews using the critical decision method with four senior physician subject matter experts. These experts are recognized by their peers for their skill in safely minimizing testing while maintaining patient safety and engagement. Focus groups and interviews were audio recorded and notes were taken by two independent note takers. Notes were entered into ATLAS.ti and analyzed using the constant comparative method of grounded theory, an iterative coding process to determine themes. Data were double‐coded and examined for discrepancies to establish consensus. Results Five core domains emerged from the analysis: establishing trust, anxiety (patient and provider), constraints related to ED practice, the influence of others, and patient expectations. Key themes within these domains included patient engagement, provider confidence and experience, ability to identify and manage patient anxiety, time constraints, concussion knowledge gap, influence of health care providers, and patient expectations to get a CT. Conclusions Despite high‐quality evidence informing use of CT in minor head injury, multiple factors influence the decision to obtain CT in practice. Identifying and disseminating approaches and designing systems that help clinicians establish trust and manage uncertainty within the ED context could optimize CT use in minor head injury.